Existence and Uniqueness of Climate-Based Periodic Chikungunya Fractional Order Model with Incubation Period - Dianavinnarasi, J.; Mariyal, J.Jency; Pratap, A. (Journal of Environmental Accounting and Management, 2026)
Chikungunya fever is caused by CHIKV, which uses the Aedes albopictus and Aedes aegypti mosquito population as a vector. According to WHO, mosquito-borne diseases cause millions of deaths. In this paper, the existence and uniqueness results of the temperature dependent Chikungunya virus dynamical model using fractional calculus and some fixed point theorems are derived. The Caputo-Fabrizio operator without singular kernel is used to obtain the solution of the proposed model.